Hard Skills dan Soft Skills pada Bagian Sumber Daya Manusia di Organisasi Industri - Muhammad Untung Manara (Jurnal Psikologi Tabularasa, 2014)
This study aimed to answer the question "what are the skills required from prospective employees for HR position ?". This study used a qualitative descriptive survey approach. The data analysis used content analysis techniques. Source of data of this study study were 100 companies who advertise job openings in online job site with HR position with any of the terms was psychology graduate. From the analysis found two categories of skills required for the position HR company that was hard skills and soft skills. Understanding of labor laws was a hard skill that has a top frequency, at 19.79 % , followed by the ability to recruit and selection (14.5 %) , training and development of employees (12.98 %), and the ability to use psychological tests (11.83 %) . Category of soft skills that has top frequency was communication skills (12.09 %) , followed by the ability to work in teams or individually (9.89 %) , ability to work under pressure (9.62 %) , and good personality (7.96%).